Germany : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper on Germany focuses on current economic condition in the country. The build-up of Germany's current account surplus over the last decade does not lend itself to a single-factor explanation, as both global and domestic factors, as well as policy changes led to increased savings and lower investment. All sectors contributed to the build-up of the surplus. Although fiscal consolidation and higher household savings played a role, the corporate sector experienced a more pronounced shift. This paper provides a retrospective on these developments and explores whether the factors contributing to the surplus are likely to be reversed going forward. Although there are common global drivers for the non-financial corporations shift to a net lender position, several German-specific factors played a role, notably the labor market reforms in the 2000s, the business tax reforms, and the globalization of German firms' production chains. The households' saving-investment gap widened in the early 2000s as the pension reforms and growing income inequality boosted households' savings and residential investment declined by the end of the reunification construction boom.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet